1993
DOI: 10.1002/ajpa.1330920104
|View full text |Cite
|
Sign up to set email alerts
|

Response of bone and enamel formation to nutritional supplementation and morbidity among malnourished Guatemalan children

Abstract: The effects of changes in nutritional and health status upon bone and enamel development are examined in a sample of 63 rural Guatemalan children (24 females, 39 males). The number of ossified hand-wrist centers at 3 years and the number of linear enamel hypoplasias (LEH) in approximately 0-3 year zones of developing teeth were used to monitor the response of bone mineralization and enamel matrix formation to illness and nutritional supplementation. Numbers of ossified centers and LEH were compared across sex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
1
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 32 publications
6
87
1
3
Order By: Relevance
“…Reports of greater female exposure to developmental instability and to episodic stress (linear enamel hypoplasiae) through socio-cultural biases have originated from historic (Bigoni et al, 2013;Šlaus, 2000) and contemporary populations (Goodman et al, 1987;Guatelli-Steinberg et al, 2006;May et al, 1993). These studies support the idea that sociocultural differences in gender roles and childcare of males and females can produce a greater susceptibility to developmental instability, which may be detected by FA in dental and mandibular morphology of the Portuguese sample.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Reports of greater female exposure to developmental instability and to episodic stress (linear enamel hypoplasiae) through socio-cultural biases have originated from historic (Bigoni et al, 2013;Šlaus, 2000) and contemporary populations (Goodman et al, 1987;Guatelli-Steinberg et al, 2006;May et al, 1993). These studies support the idea that sociocultural differences in gender roles and childcare of males and females can produce a greater susceptibility to developmental instability, which may be detected by FA in dental and mandibular morphology of the Portuguese sample.…”
Section: Discussionsupporting
confidence: 55%
“…Despite greater male susceptibility to mortality, morbidity, vulnerability and risk taking (factors that usually are not evident until adolescence: Kruger and Nesse, 2006), females in the past have been reported to be particularly susceptible to mortality, morbidity and stress due to the socio-cultural preferential treatment of males (Bigoni et al, 2013;Goodman et al, 1987;Guatelli-Steinberg et al, 2006;May et al, 1993;Šlaus, 2000). Such male preferential treatment is particularly prevalent in poverty-ridden underdeveloped countries (Goodman et al, 1987;May et al, 1993) like Portugal in the 19 th and early 20 th centuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an investigation of sex differences in LEH for a particular period in Japan has not previously been reported. Research in other countries has produced contradictory results: higher prevalence in males (Van Gerven, et al, 1990;Saunders and Keenleyside, 1999;Palubeckaite, et al, 2002), higher prevalence in females (May et al, 1993;Slaus, 2000;King, et al, 2005), and no significant differences between the sexes (Goodman et al, 1980;Lanphear, 1990;Duray, 1996;Malville, 1997;Lovell and Whyte, 1999;Slaus, 2008).…”
Section: Sex Differencesmentioning
confidence: 99%
“…Studies of living children have shown that differential treatment of males and females in childhood can predict differences in levels of LEH in adulthood (May et al, 1993). Moreover, from the investigation of enamel hypoplasia in deciduous and permanent dentition of human and nonhuman primates, Guatelli-Steinberg and Lukacs (1999) insisted that though females are better buffered against environmental stress, a weak influence of male vulnerability on the expression of enamel hypoplasia is most likely to be detected in samples of very large size (>1000 individuals), and that evidence of higher enamel hypoplasia prevalence in girls might therefore be used as a biological marker of preferential investment in sons.…”
Section: Sex Differencesmentioning
confidence: 99%